Pengembangan Instrumen Evaluasi Pembelajaran Matematika Tipe PISA Berkarakteristik Kebudayaan Lokal - Anggi Aprillia Pratiwi; Mohammad Mahfud Effendi; Siti Khoiruli Ummah (Program Studi Pendidikan Matematika UIN Raden Fatah Palembang, 2020)
The study was aimed to produce an evaluation instrument in the form of a PISA problem type mathematical problem with a valid, practical and effective local cultural context to assess students' mathematical literacy viewed from the context of local culture in Kota Batu. The research method used is research design with the type of development study which consists of two stages, namely the preliminary stage and the formative evaluation stage. The preliminary stage includes analysis of student needs, curriculum analysis, and analysis of PISA evaluation instruments. The formative evaluation stage includes self-evaluation, expert review, one-to-one, small groups and field tests. Data were collected through field test tests with three valid PISA problem type math problems at the expert review stage, practically at the small group stage, while effectively reviewed at the field test stage that was able to attract interest and motivate students so that they were challenged to complete the questions given. Students' mathematical literacy skills are found in developing strategies to solve problems.